The Role of Islamic Religious Education Teachers in Shaping Students' Character at SMK 8 Negeri Medan - Herfany, Viola Michela; Abdurrasyid, Abdurrasyid (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in shaping students' character at SMK Negeri 8 Medan. Character education is an important aspect in the formation of students' personalities, especially in the school environment. PAI teachers have a strategic responsibility in guiding, instilling moral values, and building students' character based on Islamic principles. The research method used is a qualitative approach with data collection techniques including interviews, observations, and documentation. The research informants include PAI teachers, students, and the school principal. Data were analyzed using qualitative descriptive analysis techniques to identify the strategies applied by teachers in shaping students' character. The results of the study show that PAI teachers at SMK Negeri 8 Medan play a significant role in character building by integrating Islamic values into lessons, offering a personal approach to students, and organizing religious activities such as study groups, congregational prayers, and commemorating Islamic holidays. In addition, the supportive school environment strengthens the teachers' efforts in shaping students' character. This study concludes that the role of PAI teachers is crucial in shaping students' character, not only through classroom teaching but also through role modeling, spiritual approaches, and emotional development. The recommendation of this study is to improve the training and development of PAI teachers' competencies and to strengthen collaboration between schools, parents, and the community in supporting the formation of students' character.